Pedagogical Development of Peace Values: Innovative Solutions to Overcome Bullying in the School Environment - Agnesh Prima Destiany; Pupun Nuryani; Aryanti (Nexus Publishing NXP, 2024)
This article aims at pedagogy as a science and approach to developing guidance for students, in discovering the value of peace, as a solution to overcoming the problem of bullying in the current school environment. Therefore, seeing the urgency of the importance of the value of peace, it must be processed by creating a positive learning environment, so that it can overcome the level of bullying. In other words, being able to shape future generations, related to peace and respecting human dignity holistically. Through the implementation of programs that promote the values ​​of peace, it is hoped that educational institutions can create a safer and more supportive learning environment for students. Emphasis on developing pedagogy to foster the value of peace as an innovative solution in overcoming bullying in the school environment is important in strengthening efforts to prevent and handle bullying in schools. The approach used in this research is a descriptive qualitative approach using a literature review method and field studies using observation, interviews and documentation study techniques.